2020
DOI: 10.1016/j.foodres.2019.108922
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions and acidified milk gels as a strategy for improving stability and antioxidant activity of yarrow phenolic compounds after gastrointestinal digestion

Abstract: Nanoemulsions and acidified milk gels as a strategy for improving stability and antioxidant activity of yarrow phenolic compounds after gastrointestinal digestion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Native-PAGE patterns confirmed the intensive denaturation and participation of whey proteins (β-LG and α-LA) and κ-casein in heat-induced complexes (Figure 1c, lines 2-5). Heat-induced whey protein aggregates have an increased affinity for binding phenolics and play a critical role in strengthening phenolics-casein interactions [25,26,37]. As can be observed (Figure 1c), the intensity of the bands corresponding to whey protein/casein (WP/CN) complexes of TME samples gradually increased with grape pomace seed extract amount in TME samples (TME1 < TME2 < TME3), in comparison to that of TM sample (Figure 1c, Table 3).…”
Section: Electrophoretic Analysis Of M Tm and Tme Powder Samplesmentioning
confidence: 70%
See 1 more Smart Citation
“…Native-PAGE patterns confirmed the intensive denaturation and participation of whey proteins (β-LG and α-LA) and κ-casein in heat-induced complexes (Figure 1c, lines 2-5). Heat-induced whey protein aggregates have an increased affinity for binding phenolics and play a critical role in strengthening phenolics-casein interactions [25,26,37]. As can be observed (Figure 1c), the intensity of the bands corresponding to whey protein/casein (WP/CN) complexes of TME samples gradually increased with grape pomace seed extract amount in TME samples (TME1 < TME2 < TME3), in comparison to that of TM sample (Figure 1c, Table 3).…”
Section: Electrophoretic Analysis Of M Tm and Tme Powder Samplesmentioning
confidence: 70%
“…Participation of κ-; αand β-casein in the formation of heatinduced complexes encourages better linkages and uniform distribution of micelle-bound complexes, which contribute to absence of free soluble complexes [24]. Previous reports by Rahimi Yazdi and Corredig [26] and Villalva et al [37] have shown that this heatinduced WPs complexes increased and enhanced binding affinity of casein micelles to phenolic compounds.…”
Section: Modelmentioning
confidence: 87%
“…Nano-carrier systems have shown many advantages in the encapsulation of phenolic compounds, such as uniform morphology, high encapsulation efficiency, increased solubility, thermal and storage stability, as well as improved bioactivity. 47,[49][50][51]…”
Section: Main Challenges To Using Phenolic Compounds As Functional In...mentioning
confidence: 99%
“…Nanotechnology involves various strategies using different materials at nanoscale dimensions to fabricate devices widely employed in the electronic and food industries, as well as in the pharmaceutical and biomedical fields. Nano‐carrier systems have shown many advantages in the encapsulation of phenolic compounds, such as uniform morphology, high encapsulation efficiency, increased solubility, thermal and storage stability, as well as improved bioactivity 47,49‐51 …”
Section: Main Challenges To Using Phenolic Compounds As Functional In...mentioning
confidence: 99%
“…Moreover, the higher charge on the protein surface provides further stability to the emulsion, because the adsorbed proteins have electrostatic repulsion between them, preventing flocculation and coalescence [51]. In general, polyphenolic compounds exhibit antioxidant activities [52]. The total phenolic contents of the UPP and PPN were 77.6 and 88.1 mg/g, respectively (Table 3).…”
Section: Emulsion Propertiesmentioning
confidence: 99%